Characterization of corn (Zea mays) leaf powder and its adsorption properties regarding Cu(II) and Cd(II) from aqueous samples - Silva, Adrielli C.P. [UNESP]; Jorgetto, Alexandre O. [UNESP]; Wondracek, Marcos H.P. [UNESP]; Saeki, Margarida J. [UNESP]; Schneider, José F.; Pedrosa, Valber A. [UNESP]; Martines, Marco A.U.; Castro, Gustavo R. [UNESP] (My University, 2015)
In this study, a green adsorbent made of corn leaf powder was applied in the removal of Cu(II) and Cd(II) from water samples. The material was characterized by Fourier transform infrared (FTIR) spectroscopy, which indicated the existence of amine (1375 and 1249 cm-1) and carboxylic groups (1730 cm-1). Elemental analysis corroborated the results of FTIR, indicating that the substance consisted of 0.63% sulfur and 0.46% nitrogen. The NMR results indicated that thiamine and methionine may be present in the corn leaf substances, which can act in coordination with metal species. Scanning electron microscopy (SEM) indicated the existence of pores of approximately 15 μm in diameter and a homogeneous particle size. Equilibrium adsorption was attained in 5 min, and the obtained data were applied to a pseudo-second-order kinetic model (r2 = 0.999 for Cu(II) and Cd(II)). Selective adsorption of Cu(II) was attained at pH 3.0, and the maximum adsorption capacities were attained at pH 6.0. Adsorption isotherms were adjusted to a modified Langmuir equation and the maximum number of moles adsorbed of Cu(II) and Cd(II) were 0.089 and 0.071 mmol g-1, respectively. The results are superior to many materials currently employed in metal removal from aqueous samples.
Keywords: Adsorption; Corn leaf powder; Heavy metal ions; Metal-surface interaction